Kontribusi Agroforesty Terhadap Pendapatan Rumah Tangga Petani di Desa Niukbaun, Kecamatan Amarasi Barat - Daud Arianto Robu; Wilhelmina Seran; Norman P. L. B. Riwu Kaho (Wana Lestari, 2025)
The purpose of the study was to determine the components and patterns of agroforestry that has been practiced by the people of Niukbaun Village, West Amarasi District and to find out the contribution of agroforestry to the income of farmers household in the research area. This research was carried out in Niukbaun Village, West Amarasi District, the determination of samples was carried out purposively based on certain criteria; the respondents that were selected are the people who lived near the forest and also cultivated gardens as a traditional agroforestery system. The data collection techniques used in this study are primary data and secondary data. From the data collected, quantitative descriptive data analysis was carried out. The agroforestry pattern applied by farmers in Niukbaun village is tress along the border or plants surrounded by woody plants with plant components such as eggplant (solanum melongena), selidri, onions, vegetables, corn (zea mays), carrots (daucus carota), bananas (Musa sp), jackfruit (Artocarpus heterophyllus), coconut (Cocos nucifera), white teak ( Gmelina arborea), Mahogany (Switenia mahagoni), Pecan (Aleurites moluccanus) and Asam (tamarindus indica) as for some farmers they alsoraise animals such as pigs andcattle. The total income received by farmers from agroforestry products are IDR 1,172,874,000 and non-agroforestry are IDR 26,400,000. Agroforestry income are that of non-agroforestry income. This shows that the agroforestry system greatly affects people's income in location site